Challenges and Opportunities for Start-up Innovation and Entrepreneurship as Tools Towards Knowledge-based Economy: A Study of Tribal Youth of the TSP Region of Southern Rajasthan of India. Issue 2 (June 2022) - Gupta, Sachin; Satpathy, Biswajit; Baral, Sukanta Kumar; Chaturvedi, Ankita
The goal of this study was to look at the start-up ecosystem and entrepreneurial environment among tribal youth in the Tribal Sub-Plan area of Southern Rajasthan by assessing their predicament and working conditions. The study looked at the obstacles, challenges and possibilities that start-ups and new enterprises face, as well as how they may be used to create economic, political and social change by helping society towards a knowledge-based economy. The study's goal is to underline the vital role of start-ups, and instead of seeing start-ups and challenges as two separate things, we may connect the two and 'use' start-ups to solve these problems, specifically by innovating in areas where tribal society's most pressing problems exist.